New Eocene species of the crinoid genera Holopus and Cyathidium (Cyrtocrinida: Holopodidae) from north-eastern Italy - Martinez-Soares, Pablo; Roux, Michel; Giusberti, Luca; Gatto, Roberto; Eléaume, Marc; Améziane, Nadia (Zootaxa, 2024)
Holopodidae is one of the three families in the order Cyrtocrinida that have extant representatives. Two genera have been described, Holopus and Cyathidium, both with extant species and fossil representatives dating back to the Cenomanian (Late Cretaceous). Eocene (Lutetian) holopodid material from the Chiampo Valley (north-eastern Italy) has recently been attributed to H. spileccense, the type-stratum and locality of which is the Ypresian of the nearby Spilecco Hill, and to C. gastaldii known from the Miocene of Turin. Here we describe new holopodid material from both Chiampo and Spilecco, comprising cups and numerous brachials. Using qualitative and quantitative characters, the Chiampo holopodids are deemed to be assignable to two new species: Holopus fabianii sp. nov. and Cyathidium chiampoensis sp. nov. The Chiampo material includes the first records of keystone plates and distal brachials for an extinct species of Holopus. New proximal brachials are described for H. spileccense but no keystone plate was found for this species. Access to the holotype of Cyathidium gastaldii has enabled a description of the specimen and a first diagnosis for the species. Formerly described cups, as well as a newly collected one, are attributed to Cyathidium sp. due to the lack of diagnostic characters. The affinities between H. spileccense, H. fabianii sp. nov. and the extant Indo-Pacific H. alidis suggest that these three species might share a common Gondwanan origin.